Antagonisme Marmin terhadap Reseptor 5-Hidroksi Triptamin dan Reseptor Histamin pada Otot Polos Ileum Marmut - AGUNG ENDRO NUGROHO; PUGU NOVI ARSITO; YANCE ANAS; JOKO TRI WIBOWO; SUGENG RIYANTO; MOHAMAD ASPOLLAH SUKARI (Fakultas Farmasi Universitas Pancasila, 2011)
The exploration of several active compounds of medicinal plants Aegle marmelos Correa (Rutaceae) have found marmin that strongly inhibit the histamine release from mast cells. The present study investigated the antagonism phenomena of marmin on 5-hydroxy triptamine and histamine receptors in guinea-pig ileum smooth muscle. The study was performed using isolated-organ technique in Tyrode buffer medium. The agonists used to sensitize the receptors were histamine and 5-hydroxy triptamine. The type of antagonism was identified by considering: 1). the decrease of pD2 or Emax values of agonists due to pretreatment of marmin, and 2) Schild regression method. In the study, marmin (10 and 100 mM) decreased the maximum contraction effect of 5-HT by 40% and 60%, respectively. However, marmin did not influence the pD2 value of 5-HT . On the other side, marmin did not influence the maximum contraction effect of histamine, however, decreased the pD2 value of histamine. Based on Schild regression method, the pA2 value of marmin was 0.8016. In conclusion, marmin non-competitively antagonized 5-HT 4 receptor, and competitively antagonized histamine receptor in ileum smooth muscle.